Transparent and opaque pricing: The interesting case of lithium. (September 2015) - Maxwell, Philip
Abstract: Appreciating the pricing arrangements for a mineral and its compounds provides useful insight into the nature of its market and the industrial structure of its production. This paper focuses on the case of lithium, which has emerged from being a minor metal with limited profitable applications in 1950 to its glamour metal status some 65 years later. During this period bilateral contracts based on producer prices have been the major way in which prices have been negotiated. The entry of a major new producer (SQM) in the late 1990s led to a situation where price information was difficult to obtain, even though competition in the sector was growing. This is consistent with a movement from cooperative oligopoly to non-cooperative oligopoly. Growing price transparency since 2010 has been associated with the actual and projected entry of several new producers. With its continuing growth it seems inevitable that lithium will be formally traded on one of major metal exchanges within the next decade. In addition to this, the practice of transfer pricing between branches of established multinational producers also applies to the lithium industry. Highlights: Since 1960, lithium and its compounds have experienced several pricing forms. Changing lithium pricing gives insight to the industry׳s changing structure. Secretive negotiated pricing was notable between 1998 and 2009. Producer pricing, mineral press quotes and transfer pricing also have prevailed. Market growth suggests lithium will eventually be traded on commodity exchanges.